pengaruh ukuran perusahaan, profitabilitas, solvabilitas dan aerning variability terhadap kebijakan dividen perusahaan manufaktur di daftar efek syariah (DES) periode 2012-2017 - Nanda Shelia; Ari Prasetyo (Universitas Airlangga, 2019)
This study aims to determine the effect of firm size, profitability, solvency and earnings variability to dividend policy of Manufacturing Companies in Daftar aefek Syariah (DES) period 2012-2017.This research uses quantitative approach with panel data regression analysis technique. Statistical tool used is software Stata (Statistics and Data) 14. Population in this research is a manufacturing company in Daftar Efek Syariah (DES). The sample used in this study are 19 manufacturing companies in the Daftar Efek Syariah (DES). The observation period of the study starts from 2012 to 2017. Based on the best estimation model, Random Effect Model (REM) shows that firm size, profitability, solvency and earning variability variables influence simultaneously and significantly to dividend policy of manufacturing company in Daftar Efek Syariah (DES). Partially variable of firm size and earning variability have positive and significant impact, solvability variable have a negative and significant impact, and profitability variable have an insignificant impact to dividend policy of manufacturing company in Daftar Efek Syariah (DES) period 2012-2017.Keywords: Dividend Policy, Company Size, Profitability, Solvency, Earning Variability